HERITABILITIES OF BODY SIZE BY GROWTH HORMONE (GH-Msp1) GENOTYPES USING PCR-RFLP IN ONGOLE GRADE CATTLE - Paputungan, U.; Hakim, L.; Ciptadi, G.; Lapian, H. F. N. (Diponegoro University, 2015)
Genotypic performance in term of heritability as the crucial factor of animal economical traits for body size inheritance had not been fully studied in Ongole-grade cattle. The objectives of this research were to define the heritability values of live weight, chest girth and body length in Ongole-crossbred cattle. Total of 37 blood samples were collected from parental cows and 2 blood samples from parental Ongole breed bulls. All blood samples were screened for the presence of growth hormone (GH) locus using PCR-RFLP method involving restricted enzyme Msp1 on agarose-gel (1.2%). Data were analyzed using statistical program in Excel XP. Results showed that the phenotypic estimation average of Ongole grade cattle population of live weight, chest girth and body length were 445.41 ± 45.95 kg, 175.35 ± 4.11 cm, and 139.70 ± 5.73cm, respectively. The heritability values of animal live weight, chest girth and body length in this study were 0.24, 0.003, and 0.41, respectively. These heritability values of animal live weight and body length would be categorized as moderate to high genotypic performance values, while the heritability of animal chest girth was included in low heritability standard of the animal economical trait performance.